Predicting whether songs will be hit using Logistic Regression (International Journal of Engineering and Computer Science, 2017)
This paper predicts whether a song will be super hit and will it reach it to chart buster based on several music features. It is crucial to predicting the popularity of a song, especially in a business competitive world. We will use Logistic Regression in our model to predict the probability of reaching Top 10 songs in the popularity.